1998
DOI: 10.1021/ac980117u
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Electrophoretic Determination of Different Classes of Organic Ions by Potentiometric Detection with Coated-Wire Ion-Selective Electrodes

Abstract: Singly charged amines and sulfonic acids as cationic and anionic aliphatic model substances, respectively, were detected in capillary electrophoresis with all-solid-state ion-selective electrodes. The sensitivity for these compounds is a function of their lipophilicity. The signal detected is generally greater for molecules with a larger organic part. The utility of the method is further demonstrated by the detection of a group of aromatic compounds in the form of the anionic analgesics (S)-(+)-2-(4-isobutylph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 18 publications
1
55
0
1
Order By: Relevance
“…It was, however, reported that their long-term potential stability was limited and they were, therefore, useful only in specific applications such as detectors for capillary electrophoresis [14] or in flow-injection analysis [15]. Their potential instability was attributed to lack of control of the concentrations of the species defining the redox potential at the membrane/metal interface [12,16,17] and their response characteristics were successfully improved by adding an appropriate redox-active component to the PVC membrane [18] or by using an intermediate redox-active polymer layer [19].…”
Section: Introductionmentioning
confidence: 99%
“…It was, however, reported that their long-term potential stability was limited and they were, therefore, useful only in specific applications such as detectors for capillary electrophoresis [14] or in flow-injection analysis [15]. Their potential instability was attributed to lack of control of the concentrations of the species defining the redox potential at the membrane/metal interface [12,16,17] and their response characteristics were successfully improved by adding an appropriate redox-active component to the PVC membrane [18] or by using an intermediate redox-active polymer layer [19].…”
Section: Introductionmentioning
confidence: 99%
“…Eletrodos de membrana líquida foram inicialmente empregados [232][233][234][235][236][237][238] , mas devido à sua fragilidade e dificuldade de implementação, têm sido substituídos por eletrodos metálicos recobertos com filme seletivo 33,[239][240][241][242][243][244][245][246] . Estes possuem maior robustez, facilidade de alinhamento e fabricação, além de possuírem maior tempo de vida e nível de resposta comparável com os eletrodos de membrana líqui-da.…”
Section: Detecção Potenciométrica (Pd)unclassified
“…The improved performance characteristics of the CGE over those of PME presumably originate from the coated graphite technology, where an internal 1.0 × 10 -3 M Cu(NO3)2 solution, in the case of PME, has been replaced by a copper wire of much higher electrical conductivity, in the case of CGE. 38 Interfering ion PME CGE…”
Section: +mentioning
confidence: 99%